Bioinspired Multi-Layer Biopolymer-Based Dental Implant Coating for Enhanced Osseointegration - Üzülmez, Betül; Can, Özge; Demirsoy, Zeynep; Can, Özge; Gülseren, Gulcihan (Wiley, 2023)
The major drawbacks of metal-based implants are weak osseointegration and post-operational infections. These limitations restrict the long-term use of implants that may cause severe tissue damage and replacement of the implant. Recent strategies to enhance the osseointegration process require an elaborate fabrication process and suffer from post-operative complications. To address the current challenges taking inspiration from the extracellular matrix (ECM), the current study is designed to establish enhanced osseointegration with lowered risk of infection. Natural biopolymer pectin, peptide amphiphiles, and enzyme-mimicking fullerene moieties are governed to present an ECM-like environment around the implant surfaces. This multifunctional approach promotes osseointegration via inducing biomineralization and osteoblast differentiation. Application of the biopolymer-based composite to the metal surfaces significantly enhances cellular attachment, supports the mineral deposition, and upregulates osteoblast-specific gene expression. In addition to the osteoinductive properties of the constructed layers, the inherent antimicrobial properties of multilayer coating are also used to prevent infection possibility. The reported biopolymer-artificial enzyme composite demonstrates antimicrobial activity against Escherichia coli and Bacillus subtilis as a multifunctional surface coating.
Keywords: ECM-mimic; Implant coating; Osseointegration; Pectins; Peptides